Find the inverse of the Function
0-4" id="TexFormula1" title="f(x)=\sqrt[3]{\frac{x}{9} } -4" alt="f(x)=\sqrt[3]{\frac{x}{9} } -4" align="absmiddle" class="latex-formula">
1 answer:
9514 1404 393
Answer:
D
Step-by-step explanation:
Solve x = f(y) for y.
x = ∛(y/9) -4
x +4 = ∛(y/9) . . . . . add 4
(x +4)³ = y/9 .. . . . . cube
9(x +4)³ = y . . . . . . multiply by 9
The inverse function is ...
f⁻¹(x) = 9(x +4)³ . . . . . matches the last choice
You might be interested in
B if you need an explanation just comment
Y - y₁ = m(x - x₁)
y - 2 = 4(x - 7)
y - 2 = 4(x) - 4(7)
y - 2 = 4x - 28
+ 2 + 2
y = 4x - 26
Dont quote me on this but i think it is 10 because 86 × 2 is 172 and 297 ÷ 172 is 10 I think
Answer:
d) 1⃣
Step-by-step explanation:
Multiply -5 by -2 to get , then deduct 7 to get 3. So, you now know that 3 = 3a; 1 = a.
Answer:
A
Step-by-step explanation:
5 x 2/3=3.333333333...
and 3.3333333...
is also equal to 3 1/3